Krytyczne doświadczenia życiowe jako źródło zmian: w kierunku potraumatycznego rozwoju - Wróblewska , Halina Monika (Studia Edukacyjne, 2022)
Experiencing highly stressful events need not only entail negative consequences, but may also lead to the emergence of positive change, which is referred to as post-traumatic growth. The study shows the role of subjective resources and potential in dealing with a crisis that may constitute a possible space for development. The aim of the considerations is to look at critical life experiences as a source of change. They are related to positive adaptation (resilience). Important resilience skills include reevaluation and reinterpretation of the meaning of events in the face of threats and change. Resources and subjective potential, which moderate the negative impact of threats and adversities, help to determine positive orientation, creative human activity and the ability to transgressive actions